#1**+1 **

The average of x + 6,6x + 2, and 2x is 4x-7. What is x?

In order to find the average of the numbers you have to add all of them and then divide by the amount of numbers you have to average.

First,

[(x + 6) + (6x+2) + 2x ]/3 = 4x-7

Getting rid of the denominator, by multiplying by 3 on both sides,

[(x + 6) + (6x+2) + 2x ] = 12x - 21

Grouping all the x's

[(x + 6x + 2x) + 8] = 12x - 21

[9x+8] = 12x -21

-3x = -29

**x = 29/3**

Hope I didin't make any silly mistakes lol.

Zenitsu Oct 18, 2021